2011
DOI: 10.1007/82_2011_175
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenetic Landscape of Lineage Choice: Lessons From the Heritability of Cd4 and Cd8 Expression

Abstract: Developing αβ T cells choose between the helper and cytotoxic lineages, depending upon the specificity of their T cell receptors for MHC molecules. The expression of the CD4 co-receptor on helper cells and the CD8 co-receptor on cytotoxic cells is intimately linked to this decision, and their regulation at the transcriptional level has been the subject of intense study to better understand lineage choice. Indeed, as the fate of developing T cells is decided, the expression status of these genes is accordingly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 124 publications
0
13
0
Order By: Relevance
“…1H). To evaluate this possibility, we generated Cd4 -Cre Thpok fl/fl Cd4Sil fl/+ mice, in which Cre excises floxed alleles of Thpok and of the Cd4 silencer ( Cd4Sil ), a cis-regulatory element mediating Cd4 silencing in differentiating CD8 + -lineage thymocytes (39, 40). Even though silencer inactivation maintained CD4 expression, it failed to rescue Treg cell populations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1H). To evaluate this possibility, we generated Cd4 -Cre Thpok fl/fl Cd4Sil fl/+ mice, in which Cre excises floxed alleles of Thpok and of the Cd4 silencer ( Cd4Sil ), a cis-regulatory element mediating Cd4 silencing in differentiating CD8 + -lineage thymocytes (39, 40). Even though silencer inactivation maintained CD4 expression, it failed to rescue Treg cell populations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that chromatin modification at the CD4 locus may correlate with CD4 transcription. To further test this, we analyzed the CD4 gene promoter (P), 5′enhancer (two separate amplicons, E1 and E2), and silencer (S) for chromatin marks associated with active and repressed transcription (33). We performed multiple independent chromatin immunoprecipitations (ChIP) followed by quantitative PCR for E, P, and S regulatory elements as well as for exons 2 and 10 (ex.2, ex.10).…”
Section: Resultsmentioning
confidence: 99%
“…Most remarkably, the 32080 line has cell-to cell variation in CD4 expression that resembles epigenetic variegation (36). The CD4 gene is known to be epigenetically regulated during normal T-cell ontogeny and the 32080 line provides a remarkable model for the developmental switch between two T-cell progenitor stages, the intermediate CD8 single positive (ISP) stage and the double positive (DP) stage (33). Unlike normal development, however, the 32080 CD4 - and CD4 + populations interconvert (Figure 7D).…”
Section: Discussionmentioning
confidence: 99%
“…In the immune system, the best-characterized example of epigenetic regulation concerns the silencing of the Cd4 gene in CD8+ thymocytes. A dedicated silencer region in the Cd4 locus is known to play a central role in the initiation of Cd4 silencing during CD8+ T cell development [14]. However, in mature CD8+ T cells, the silent state of the Cd4 locus and the chromatin properties that characterize the silent state can be stably maintained in the absence of the silencer [14, 15].…”
Section: The Challenges Of Embracing Complexitymentioning
confidence: 99%
“…A dedicated silencer region in the Cd4 locus is known to play a central role in the initiation of Cd4 silencing during CD8+ T cell development [14]. However, in mature CD8+ T cells, the silent state of the Cd4 locus and the chromatin properties that characterize the silent state can be stably maintained in the absence of the silencer [14, 15]. This finding suggests that the silencer helps establish a repressive chromatin structure that is stably maintained by a true epigenetic mechanism.…”
Section: The Challenges Of Embracing Complexitymentioning
confidence: 99%